2010
DOI: 10.1039/c0cc00596g
|View full text |Cite
|
Sign up to set email alerts
|

Pdop layer exhibiting zwitterionicity: a simple electrochemical interface for governing ion permeability

Abstract: Polydopamine film which contains amine groups and phenolic hydroxyl groups exhibits fully reversible, pH-switchable permselectivity for both cationic and anionic redox-active probe molecules. At high pH the film has a net negative charge that excludes anions but passes cations; at low pH it is positively charged and excludes cations but passes anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
201
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(215 citation statements)
references
References 33 publications
12
201
0
2
Order By: Relevance
“…However, silver is leached in the bacterial suspension and a second reduction step of Ag + cations in Ag is not possible [83,99] Membranes for separations and fuel cells Modification of a polysulfone membrane to make it permselective [78] The permselectivity of polydopamine is pH dependent and also depends on the synthesis method [79,80] Improvement of methanol barrier in fuel cells [102] Films for sensing Highly selective sensing of an analyte can be obtained by imprinting the molecule of interest in the polydopamine film during its formation [104][105][106] Coating of particles for the production of hollow capsules…”
Section: Discussionmentioning
confidence: 99%
“…However, silver is leached in the bacterial suspension and a second reduction step of Ag + cations in Ag is not possible [83,99] Membranes for separations and fuel cells Modification of a polysulfone membrane to make it permselective [78] The permselectivity of polydopamine is pH dependent and also depends on the synthesis method [79,80] Improvement of methanol barrier in fuel cells [102] Films for sensing Highly selective sensing of an analyte can be obtained by imprinting the molecule of interest in the polydopamine film during its formation [104][105][106] Coating of particles for the production of hollow capsules…”
Section: Discussionmentioning
confidence: 99%
“…[24] Importantly, we have reported that polydopamine film exhibits zwitterionicity because Pdop molecules have a great deal of amino groups and phenolic groups; they are positively charged because of protonation of the amino group at low pH, while at high pH, they are negatively charged due to deprotonation of the phenolic group ( Figure 1A). [25] Therefore, the charged states of the Pdop coatings are supposed to impact the uptake and release characters of charged molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[58,79] Polydopamine, a synthetic melanin analog, has been used to selectively extract and separate metal cations from aqueous solutions, leveraging on the different binding affinities of the pigments toward different cations. [67,100,101] Films of polydopamine can reduce Ag + cations into Ag nanoparticles, which impart antibacterial properties to the same films. [83] Self-assembled molecular networks of indole-2-carboxylic acid (I2CA, i.e., melanin's monomer DHICA lacking the two hydroxyl phenolic groups) have been investigated on Au (111) surfaces: I2CA showed, both in ultrahigh vacuum and at liquid/solid interfaces, hydrogen-bonded assemblies from molecular dimers, [102] the next step being the same study with DHI and DHICA.…”
Section: Introductionmentioning
confidence: 99%